A análise de quadrinhos japoneses sob a ótica de Bakhtin: o mangá como material de referência para a cultura japonesa - Mussarelli, Felipe (Universidade Federal de São Carlos, 2013)
This paper seeks to find in manga (japonese comic books) published in Brazil, references to pop and popular culture of Japan that adds to them encyclopedic features. Assumptions initially depart from recent studies in science, technology and society (STS) that seeks to launch new looks for science and research, indicating that they can be carried in places and through different means. We will seek aid in theories of russian philosopher Mikhail Bakhtin about the studies on the speech genres, trying to find what is peculiar to the manga compared to other forms of comics, and the studies of dialogism, aimed at finding the different voices in the creation of manga and Japanese manga published in Brazil. Through these theoretical and methodological precepts of Bakhtin and studies in science, technology and society, we expect to find in manga published in Brazil, originally published from 2000, and then selecting those whose narratives are closer to everyday topics and or historical elements of its constitution as generic themes, imagery and verbal statements, footnotes, glossaries information in, suggesting references to japonese popular culture and pop. We expect this research to contribute to studies on the manifestations of language as well as studies on STS related mainly in cultural communication.
The analysis of japanese comics from the perspective of bakhtin: the manga as reference material for the japanese culture
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Bakhtin, Mikhail Mikhailovitch, 1895-1975; Gênero do discurso; Dialogia; Quadrinhos japoneses; Cultura japonesa; Bakhtin; Speech Genres; Dialogia; Science Technology and Society; Manga; Japonese Culture; LINGUISTICA, LETRAS E ARTES::LINGUISTICA